Character Constellations : Representations of Social Groups in Present-Day Dutch Literary Fiction - Smeets, Roel (Book collections on Project MUSE., 2021)
Fiction has a major social impact, not least because it co-shapes the image that society has of various social groups. Drawing on a collection of 170 contemporary Dutch-language novels, 'Character Constellations' presents a range of data-driven, statistical models to study depictions of characters in terms of gender, race, ethnicity, class, age, sexuality, and other identity categories. Incorporating the tools of network analysis, each chapter highlights an aspect of fictional social networks that affects the representation of social groups: their centrality, their communities, and their conflicts. While reading individual novels in light of emerging statistical patterns, combining the formal methods of social network analysis with the interpretive tools of narratology, this study shows how central societal themes such as (in)equality and emancipation, integration and segregation, and social mobility and class struggle are foregrounded, replicated, or distorted in the Dutch novel.0Showcasing what character-based critiques of literary representation gain by integrating data-driven methods into the practice of critical close reading, 'Character Constellations' contributes to societal debates on cultural representation and identity and the role fiction and art have in those debates.